2014
DOI: 10.1007/s00296-014-3127-7
|View full text |Cite
|
Sign up to set email alerts
|

Hypermobility and joint hypermobility syndrome in Brazilian students and teachers of ballet dance

Abstract: The current literature has been discussing the risks and benefits of joint hypermobility (JHM) for careers in ballet This study aimed to evaluate the prevalence of JHM and joint hypermobility syndrome (JHS) in a group of ballet teachers and students, looking both at aspects related to the flexibility required to dance, as at the risk of injuries when hypermobility is associated with other symptoms, in the case of JHS. We evaluated ballet teachers and ballet students, with age ranging from 18 to 40 years. All p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
17
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 19 publications
2
17
0
1
Order By: Relevance
“…Conditions such as tendinitis, bursitis, fasciitis, and fibromyalgia correspond to 25% of referrals to rheumatologists. The association with generalized and localized joint hypermobility, repetitive strain activities, and pain in areas of localized hypermobility [47], has been explored in professional artistic activities such as ballet, gymnastics, and acrobatics [48,49], predisposing to pain and injury due to associated mechanical trauma,.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Conditions such as tendinitis, bursitis, fasciitis, and fibromyalgia correspond to 25% of referrals to rheumatologists. The association with generalized and localized joint hypermobility, repetitive strain activities, and pain in areas of localized hypermobility [47], has been explored in professional artistic activities such as ballet, gymnastics, and acrobatics [48,49], predisposing to pain and injury due to associated mechanical trauma,.…”
Section: Discussionmentioning
confidence: 99%
“…In a Brazilian study, the prevalence of hypermobility in academic ballet activity was 58%, with a higher frequency among teachers compared with students [49]. It is also interesting to observe the performance of flute players, who have particularly greater range of motion in the hands, and even finger hypermobility, presenting more accurate proprioception through training, which is an ideal model to study the interaction between localized flexibility and joint proprioception [50].…”
Section: Discussionmentioning
confidence: 99%
“…The present study demonstrates results similar to those of prior studies, with generalized joint hypermobility in 65.6% of dancers and joint hypermobility syndrome in 31.3%. 25,35,41,44 However, no association was found between CTD gene variants and hypermobility scores. This does not mean that these gene variants do not influence dancers' mobility.…”
Section: Discussionmentioning
confidence: 95%
“…Multiple previous studies have demonstrated a higher prevalence of hypermobility spectrum disorder (HSD; formerly, generalized joint hypermobility or benign joint hypermobility syndrome) in ballet dancers as compared with controls, ranging from 24% to 92%. 6,7,25,35,41,43,44,47 These conditions are considered genetically determined. 30,66 Additionally, hypermobile Ehlers-Danlos syndrome (formerly, Ehlers-Danlos hypermobility type) is synonymous with HSD but lacks any known genetic variant.…”
mentioning
confidence: 99%
“…Penelitian ini juga sejalan dengan penelitian oleh Sanches yang meneliti prevalensi GJH pada pelatih dan penari balet di Brazil. Sanches menemukan hasil 58% total sampel memiliki GJH 16 . Populasi yang berisiko tinggi terhadap GJH adalah penari.…”
Section: Diskusiunclassified